Pembuatan Biodiesel Dari Minyak Jarak Pagar Dengan Katalis La/NZA - Irnaliah, Irnaliah; Bahri, Syaiful; Khairat, Khairat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Biodiesel is an alternative energy to replace fossil fuels. It can be made by transesterification process of vegetable oils such as jatropha oil. During the process of making biodiesel it using homogeneous catalyst such as NaOH or KOH. But homogeneous catalyst has disadvantages the formation of side product and complexity the separation of catalyst. Therefore, in this study the use of heterogeneous catalyst La/NZA was developed to produced biodiesel. The purpose of this research were produce biodiesel from jatropha oil, study the effect of mole ratio of oil/methanol and concentration of catalyst on yield of biodiesel, determine the best conditions for biodiesel production and to identify the characteristics of biodiesel produced.In the transesterification process, concentration of catalyst and mole ratio oil/methanol was variated. Yield of biodiesel based on product methyl ester and selectivity is calculated.Keyword: biodiesel, esterification, heterogeneous, transesterification